Being a Mother, Student, and Educator: Graduate Student-Mothers' Parenting Experience During COVID-19 Pandemic - Bewizta Maurilla Hasyyati; Retno Hanggarani Ninin (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
COVID-19 pandemic has been a life-changing experience in many families, affecting parents whose current responsibilities are not only being caregivers, but also educators to their children who are forced to learn from home. This situation deeply affects student mothers who have multiple roles at home, which are maintaining a postgraduate study, being housewives, and accompanying their children in online learning. This study aims to explore the lived experience of student mothers in parenting their school-age children during the pandemic, which is viewed from the quality of parenting (positive and negative parenting) and parenting stress perceived by mothers during the home learning activities. The participants were four mothers who are currently undergoing postgraduate study and have children enrolled in kindergarten and primary school (grade 1-3), and learning from home during the pandemic. The method used is qualitative, with an exploratory approach. The data were obtained through online semi-structured interviews and processed using thematic analysis methods. There are 7 themes emerged from the results, which are: 1) balancing multiple responsibilities, 2) experience in educating children from home, 3) adjusting parent expectations, 4) changes in social relationships , 5) agreements about screen time, 6) eating behaviors and physical exercises, 7) setting up new routine. These themes which will be discussed further, along with their implications for the parents’ psychological well-being.